The financial leverage of large Portuguese firms in the European context - Limão, Francisco Ferreira (2016)
The Financial Leverage of Large Portuguese Firms in the European Context This paper studies the leverage, cost of debt servicing ability and structure of debt maturity of large Portuguese firms, over the pre-crisis (2006-2009) and post-crisis (2010-2013) periods through a comparative analysis with other European peers. We document that large Portuguese firms have been reducing their leverage since the end of 2009. We find that this decrease in leverage is not a consequence higher Equity levels but rather a result of asset’s downsizing. We also document that Portuguese firms are still more leveraged than their European peers, even though this difference has decreased over time. High corporate debt levels are transversal across industries.